Verifikasi Metode Analisis Larutan Quercetin Menggunakan Spektrofotometer UV-Vis (T60) - Muhammad Andi Chandra (Universitas Borneo Lestari, 2023)
Quercetin has many health benefits including: antidiabetic, antiobesity, antioxidant, antiviral, anti-inflammatory, anticancer. The use of quercetin is due to quercetin is a flavonoid compound that is found in almost higher plants, and has strong antioxidant activity. Method Validation is also the main regulatory requirement in pharmaceutical analysis with compliance as per the guidelines or chapter any pharmacopeia of the same scope. Verification of analytical methods aims to ensure that analysts can apply analytical methods properly and guarantee the quality of test results. Verification of the analytical method of quercetin in phosphate buffer pH 7.4 using a UV-vis spectrophotometer (T60) it can be concluded that the linearity parameters, detection limit (LOD), quantification limit (LOQ), accuracy and precision have met the requirements with the following sequential results. ; 0.9995;1.427;4,326;102;0.273. The results of the verification of this analytical method are expected to be applied in the analytical method properly and ensure the quality of the test results.